Eco-SiC reinforced aluminium matrix composite for motorbike brake disc application - Maleque, Md. Abdul; Paijan, Lailatul Harina; Abdul Rahman, Nurfarina; Halim, Zahurin (2018)
This invention focused on the development of light weight eco-SiC reinforced composite material for motorbike brake disc application using cost-effective powder metallurgy process. The strategy is to reduce the weight of the current brake disc which consumes more fuel and emits more exhaust gas. Moreover, lower thermal conductivity of cast iron generates non-uniform distribution of heat on the surface during sliding leading to the hot spot. Salient features of the composite material are: Lighter weight Energy efficient; higher thermal conductivity More durable Environmental friendly Eco-SiC (extracted from waste rice husk).